The German labor market during the Great Recession: Shocks and institutions - Britta Gehrke; Wolfgang Lechthaler; Christian Merkl (Friedrich-Alexander-Universität Erlangen-Nürnberg, Institute for Economics, 2017)
This paper analyzes Germany's unusual labor market experience during the Great Recession. We estimate a general equilibrium model with a detailed labor market block for post-unification Germany. This allows us to disentangle the role of institutions (short-time work, government spending rules) and shocks (aggregate, labor market, and policy shocks) and to perform counterfactual exercises. We identify positive labor market performance shocks (likely caused by labor market reforms) as the key driver for the "German labor market miracle" during the Great Recession.
Keywords: E24; E32; E62; J08; J63; 330; Great Recession; search and matching; DSGE; short-time work; fiscal policy; business cycles; Germany